Large-area vertically aligned 2D MoS2 layers on TEMPO-cellulose nanofibers for biodegradable transient gas sensors. (19th November 2022) - Yoo, Changhyeon; Yoon, Jaesik; Kaium, Md Golam; Osorto, Brandon; Han, Sang Sub; Kim, Jung Han; Kim, Bo Kyoung; Chung, Hee-Suk; Kim, Dong-Joo; Jung, Yeonwoong
Abstract: Crystallographically anisotropic two-dimensional (2D) molybdenum disulfide (MoS2 ) with vertically aligned (VA) layers is attractive for electrochemical sensing owing to its surface-enriched dangling bonds coupled with extremely large mechanical deformability. In this study, we explored VA-2D MoS2 layers integrated on cellulose nanofibers (CNFs) for detecting various volatile organic compound gases. Sensor devices employing VA-2D MoS2 /CNFs exhibited excellent sensitivities for the tested gases of ethanol, methanol, ammonia, and acetone; e.g. a high response rate up to 83.39% for 100 ppm ethanol, significantly outperforming previously reported sensors employing horizontally aligned 2D MoS2 layers. Furthermore, VA-2D MoS2 /CNFs were identified to be completely dissolvable in buffer solutions such as phosphate-buffered saline solution and baking soda buffer solution without releasing toxic chemicals. This unusual combination of high sensitivity and excellent biodegradability inherent to VA-2D MoS2 /CNFs offers unprecedented opportunities for exploring mechanically reconfigurable sensor technologies with bio-compatible transient characteristics.